Sosialisasi dan Pelatihan Pembuatan Pakan Alternatif dengan Memanfaatkan Limbah Kulit Kopi untuk Ternak Kambing di Kelompok Ternak Raharja - Yuli Retnani; Heri Ahmad Sukria; Indah Wijayanti; Nissa Nurmilati Barkah; Taryati Taryati; Muhammad Dimas Erlangga; Mahirah Firadus (Institut Pertanian Bogor, 2026)
Margamulya Village is a center for producing green coffee beans that faces problems in managing coffee husk waste from coffee grinding. On the other hand, many residents have livestock businesses, so coffee husk waste has the potential to become alternative feed for ruminants, especially goats and sheep. This community service program aims to improve farmers' knowledge and skills in utilizing coffee husks as an alternative feed ingredient. The activities were carried out in several stages, namely observation, socialization and discussion, identification of coffee husks, processing training, feed administration assistance, and evaluation through pre-tests and post-tests. The program was attended by 40 farmers from the Raharja livestock group in Ciwidey, Bandung, West Java. The results of the activities showed a positive impact in the form of a 30% reduction in coffee husk waste used as livestock feed mixture, as well as an increase in the availability and quality of livestock feed. The main obstacle in the implementation was the limited tools and space for drying coffee husks. As a follow-up, this program encourages the continuity of feed processing from upstream to downstream. This initiative is a concrete step in creating sustainable feed based on local materials that were previously not optimally utilized. The series of community service activities that have been carried out have increased farmers' knowledge regarding the use of coffee husk waste as an alternative feed material and produced alternative feed based on coffee husk waste.